Pengaruh Penambahan Em4 Pada Limbah Cair Tahu Terhadap Biogas - ANGGRAENI, ANI; Mulyadi (Universitas Nusa Putra, 2023)
Tofu is a type of food that is familiar to Indonesian people. From the processing process it has waste. In general, tofu solid waste can be used for animal feed. Meanwhile, tofu waste in liquid form is discharged into the waters resulting in a negative impact on water quality resulting in a foul odor in the river from the tofu liquid waste. Liquid tofu waste can actually be used as biogas energy, but it is very rare because it requires a lot of money. The sole independent male tofu factory located in Kp Salakopi RT 02 / RW 12, Des. Haur Wangi, West Java, which already has a biogester tube from a government program so that tofu liquid waste can be used as biogas, but the biogas produced is not optimal. Therefore the researchers conducted research by adding EM4 biogester to tofu liquid waste as much as 0.2% in a holding pond of 6X3X0.1 = 1.8 X 1000 = 1800 Liters of tofu liquid waste from 10 December 2022 to 21 January 2023. From the results of the reset, the results of the initial test results showed that the average pressure produced was only 0.8 Bar and the average pressure generated after the addition of EM4 bioactives became 1.5 Bar. The characteristics of the premix fire produced by tofu liquid waste biogas is blue, smells bad , and not smoky.